Thermal Comfort Simulation Based on Digital Simulation: Case Study of IPB Vocational Coffee Cafe, Bogor - Zahra, Nasywa Az; Anita, Juarni; Sopiandi, Andri (Lakar: Jurnal Arsitektur, 2025)
Bogor has high annual rainfall, which affects indoor humidity levels and impacts thermal comfort. This study aims to analyze the thermal comfort conditions at Kafe Kopi Vokasi IPB using digital simulation. The research combines qualitative and quantitative methods, utilizing Ecotect Analysis software to simulate temperature, humidity, and airflow. The study examines critical parameters such as Mean Radiant Temperature (MRT), Predicted Mean Vote (PMV), and Predicted Percentage of Dissatisfied (PPD). Results indicate that the dining area maintains a neutral PMV of 0 and 0% PPD, while service and toilet areas experience discomfort with PMV values exceeding 2.5 and PPD reaching nearly 99%. These findings suggest inadequate ventilation in certain zones, leading to increased heat and humidity retention. As a solution, passive design strategies, such as enhancing natural ventilation through cross-ventilation techniques and integrating shading elements, are recommended. This research contributes to the discourse on tropical climate architecture by demonstrating the effectiveness of digital simulation in optimizing indoor environmental quality.